Enhanced efficiency of DSSC through AC-electrophoretic hybridization of TiO2 nanoparticle and nanotube. (1st September 2017) - Rezaei, Behzad; Mohammadi, Ismaeil; Ensafi, Ali Asghar; Momeni, Mohammad Mohsen
Graphical abstract: Highlights: Fabrication of free standing TNT membrane and integration in front-side illuminated DSSC. TiO2 nanoparticles were successfully filled into TNT arrays by three different technique. Investigation the different hybridized structure of photoanode on DSSC. The PCE of the DSSC was improved by 95% via EPD hybridization technique. Abstract: In this study, an efficient hybrid photoanode consisting of freestanding TiO2 nanotube (TNT) membranes and TiO2 nanoparticles (TNPs) was fabricated by high-frequency AC-electrophoresis deposition (TNT-TNP-EPD). The photovoltaic performance, transient properties and electron transport resistance of TNT-TNP-EPD photoanode were analyzed by photocurrent density-voltage (I–V) curve, open circuit voltage decay (OCVD) measurements and electrochemical impedance spectra (EIS). The power conversion efficiency (PCE) of dye-sensitized solar cell (DSSC) fabricated by bare TNT (TNT-B) was significantly improved up to 95% by AC-EPD introducing the TiO2 nanoparticles into the photoanode. The efficiency enhancement is due to produce the very uniform film with a high active surface area which is in turn due to the very regular arrangement of deposited particles by modulated high-frequency AC-EPD. This procedure was compared with doctor blade hybridization (TNT-TNP-DB photoanode) and TiCl4 sol treatment (TNT-TiCl4 photoanode) methods The TNT-TNP-EPD photoanode shows higher PCE than the others. Moreover, the EIS results show that TNT-TNP-EPD has better electron transport than other ones; 31.65 vs. 44.69, 56.86 and 67.34 Ω for TNT-TNP-DB, TNT-TiCl4, and TNT-B, respectively. However, the recombination rate of TNT-TNP-EPD is higher than TNT-B and TNT-TiCl4 which can be attributed to the increase of grain boundaries with introducing TNP to the TNT arrays. Nonetheless, the recombination rate of TNT-TNP-EPD is lower than TNT-TNP-DB due to greater uniformity of the nanoparticles in AC-EPD.